2008
DOI: 10.1007/s11630-008-0368-3
|View full text |Cite
|
Sign up to set email alerts
|

Rotating instability in the vaneless diffuser of a radial flow pump

Abstract: The paper refers to the behavior of a vaneless diffuser of a radial flow pump in partial flow operating conditions. Some experimental data have been obtained using 2D/2C PIV and unsteady pressure measurements within the diffuser, in various operating conditions. The experimental results at the lower flow rate are compared with two-dimensional numerical calculations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 13 publications
3
24
0
Order By: Relevance
“…At partial load and in particular at 0.26 Q des , previous analyses showed that a rotating instability developed in the vaneless diffuser [Dazin et al, 2008].…”
Section: Constant Angular Velocity Phenomenamentioning
confidence: 97%
See 1 more Smart Citation
“…At partial load and in particular at 0.26 Q des , previous analyses showed that a rotating instability developed in the vaneless diffuser [Dazin et al, 2008].…”
Section: Constant Angular Velocity Phenomenamentioning
confidence: 97%
“…13) [Dazin et al 2008. The spectrum at design flow rate was clearly dominated by the blade passage frequency f b (7·f imp ).…”
Section: Constant Angular Velocity Phenomenamentioning
confidence: 99%
“…The spectrum information which was acquired by two microphones allows to detect the development of rotating stall in the vaneless diffuser and also to analyze its characteristics [12,25,26], as shown in figure 2, where ψ was defined as:…”
Section: Characteristics Of Rotating Stallmentioning
confidence: 99%
“…For two dimensional analysis, it was suggested the 2D core flow instability might be responsible for rotating stall. Generally, it is admitted that the effect of [11], Dazin et al [1,12], Dodds and Vahdati [13,14], Ferrara et al [15,16], Abdelhamid et al [17][18][19], Abidogun [20], Nishida and Kobayshi [21,22], Cellai et al [23], Tsurusaki et al [24], Suzuki et al [25], Caignaert et al [26]. The main research contents of these experimental studies were focused on several aspects: i.…”
Section: Introductionmentioning
confidence: 99%
“…These effects are not taken into account with the 2D inviscid approach. In the work by [12] the Navier-Stokes equations were averaged with the Reynolds decomposition resulting in the need for turbulence closure modeling. They employed a two equation isotropic turbulence model.…”
Section: Introductionmentioning
confidence: 99%